1965
DOI: 10.3758/bf03343510
|View full text |Cite
|
Sign up to set email alerts
|

Developmental level and concept learning: Interaction of age and complexity

Abstract: A study utilizing 60 children demonstrated a strong interaction effect between developmental level and problem complexity on trials to solution of a relational concept forma~ion problem. Some S's from both developmental groups were unable to verbalize the concept even though meeting a "trials correct" criterionofsolution. Problem Klugh et al (1964) have reported data which indicates an inversion of the expected relationship between developmental level and trials to solution of a concept problem. In two studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1971
1971

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Te question the interaction of age and intellectual ability reported by Klugh et al (1964Klugh et al ( , 1965, Friedman (1965), and Pishkin & Rosenbluh (1966).…”
Section: Comment On Developmental Level and Concept Learning: A Possimentioning
confidence: 96%
“…Te question the interaction of age and intellectual ability reported by Klugh et al (1964Klugh et al ( , 1965, Friedman (1965), and Pishkin & Rosenbluh (1966).…”
Section: Comment On Developmental Level and Concept Learning: A Possimentioning
confidence: 96%
“…Comment on developmental level and concept learning: A possible artifact by H. E. Klugh Te Vault et al (1966) question the interaction of age and intellectual ability reported by Klugh et al (1964Klugh et al ( , 1965, Friedman (1965), and Pishkin & Rosenbluh (1966).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing theoretical and empirical interest in children's conceptual performances, and most investigations have reported positive relationships between age (chronological and mental) and degree of conceptual proficiency (e.g., Long, 1940;Long & Welch, 1941;Osier & Fivel, 1961;Piaget, 1930;Sigel, 1953). The direction of this developmental relationship is not invariant, however, as attested to by some recent work which demonstrated that older children may be inferior to younger children when more complex stimuli are employed (e.g., Friedman, 1965;Klugh & Roehl, 1965;Osier & Kofsky, 1965;Osier & Trautman, 1961).…”
Section: Role Of Irrelevant Cues In the Formation Of Concepts By Lowe...mentioning
confidence: 99%